Can direct union elections increase workers’ economic wellbeing in China?: testing effects and explaining mechanisms - Le, Junjie; Liu, Qiong; Zhou, Minghai (Unpublished, 2019)
Direct union elections, a new institutional arrangement in grassroots trade unions in China, have been introduced experimentally in coastal regions since 2000. Using matched employer–employee data, this study examines the effects of direct union elections on workers’ economic wellbeing. Results reveal that 1) union members with directly elected leaders receive higher wages than those without and 2) direct union elections are positively correlated with worker satisfaction. Additional evidences suggest that effects of direct elections work through stronger union leadership and harmonious industrial relations, resembling the voice-response face of unionism. The effect of direct elections significantly weakens or disappears when we exclude the large firms from the analysis. Meanwhile, the effect of union membership regains its significance. We argue that direct elections are a government-sponsored experiment in which large firms are selected to form an incentive-compatible framework among local governments, firms, and workers for explaining union effects with Chinese characteristics.